The role of the volleyball game and specific means of prevention an rehabilitation of cardiovascular patients - Mihai Airinei (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Practicing physical exercise plays an important role in preventing arterial wall structure changes during the process of atherosclerosis. Patients who after an accident coronial acute continue to provide a physical exercise and lead an active life, have a life quality much better, approximately normal integrating in the family and society than those who have abandoned the physical effort. So we can say that physical recovery is indispensable for all cardiac patients and especially patients with cardiac disease ischemic. This must be part of any therapeutic program prescribed to cardiac patients